Tourism in Southeast Asia a new direction - Chon, K. S. (Kaye) (Haworth Hospitality Press, 2000)
"Here is the essential guide to the exploding tourism and hospitality industries in Southeast Asia and Indochina.You will discover unique cultural aspects of various countries in the region and the impact they can have on tourism and hospitality, as well as industry overviews and current and anticipated trends." "Some of the topics explored in Tourism in Southeast Asia: A New Direction are : cross-border cooperation between Southeast Asian countries; ecotourism opportunities for local communities; existing tourism organizations; the vulnerability of current tourism policies and suggestions for change; the impact of tourism on local communities; and the flow of tourism between Australia and Southeast Asia."--Jacket